Harnessing the potential of data visualization and narratives produced by media and public actors in times of pandemic or health crisis - (:unkn) unknown (My University, 2026)
During the Covid-19 pandemic, data became central to public life. Figures on cases, deaths, hospitalisations, vaccination and ICU occupancy were published daily, discussed by journalists, cited by politicians and followed by millions of citizens. Yet data are not neutral reflections of reality: they depend on definitions, collection procedures, institutional choices and publication formats. Having access to data is therefore not enough: they must also be understandable, well documented and properly contextualized. The PANDA project studied the full communication chain of pandemic data, from production to public interpretation. It combined several methods: a computational and manual analysis of 36,724 Covid-19-related articles published by five French-speaking Swiss media outlets between January 2020 and December 2022, including 813 dynamic data visualizations; 34 qualitative interviews with journalists and institutional actors; four online experiments and a survey examining how audiences interpret and evaluate data visualizations; and the design and testing of two interactive tools aimed at improving the reading of data-driven news articles. The project focused on three interconnected questions. How did journalists and public institutions produce, access and mediate pandemic data? How did visual formats shape public understanding of the crisis? And under what conditions do audiences trust, interpret and engage with data visualizations, especially when uncertainty is involved?
Keywords: pandemie; crise sanitaire; covid-19; data; données; journalisme de données; indicateurs; data literacy; datavisualisation; communication